Human adipose stem cells cell sheet constructs impact epidermal morphogenesis in full-thickness excisional wounds - Cerqueira, M. T. (2013)
Among the wide range of strategies to target skin repair/regeneration, tissue engineering (TE) with stem cells at the forefront, remains as the most promising route. Cell sheet (CS) engineering is herein proposed, taking advantage of particular cell-cell and cell-extracellular matrix (ECM) interactions and subsequent cellular milieu, to create 3D TE constructs to promote full-thickness skin wound regeneration. Human adipose derived stem cells (hASCs) CS were obtained within five days using both thermoresponsive and standard cell culture surfaces. hASCs-based constructs were then built by superimposing three CS and transplanted into full-thickness excisional mice skin wounds with delayed healing. Constructs obtained using thermoresponsive surfaces were more stable than the ones from standard cell culture surfaces due to the natural adhesive character of the respective CS. Both CS-generating strategies lead to prolonged hASCs engraftment, although no transdifferentiation phenomena were observed. Moreover, our findings suggest that the transplanted hASCs might be promoting neotissue vascularization and extensively influencing epidermal morphogenesis, mainly through paracrine actions with the resident cells. The thicker epidermis, with a higher degree of maturation characterized by the presence of rete ridges-like structures, as well as a significant number of hair follicles observed after transplantation of the constructs combining the CS obtained from the thermoresponsive surfaces, reinforced the assumptions of the influence of the transplanted hASCs and the importance of the higher stability of these constructs promoted by cohesive cell-cell and cell-ECM interactions. Overall, this study confirmed the potential of hASCs CS-based constructs to treat full-thickness excisional skin wounds and that their fabrication conditions impact different aspects of skin regeneration, such as neovascularisation, but mainly epidermal morphogenesis.